1992
DOI: 10.1159/000126263
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Luteinizing Hormone Secretion during Food Restriction in Male Rhesus Monkeys (<i>Macaca mulatta</i>): Failure of Naloxone to Restore Normal Pulsatility

Abstract: Short periods of fasting have been shown to cause a significant slowing of pulsatile LH secretion in men and male rhesus monkeys, which appears to result from a slowing of GnRH drive to the reproductive axis. To determine whether an increased activity of endogenous opioid peptides causes this slowing of pulsatile LH secretion, the ability of naloxone administration to reverse the fasting-induced suppression of LH secretion was tested. For this study, 6 adult male rhesus monkeys, with indwelling femoral and jug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
(42 reference statements)
1
12
0
Order By: Relevance
“…Consistent with the observations in this study, LH pulse frequency was unchanged in obese men after a 10-day fast [46], in young men following either a 2-day [48]or a 5-day fast [44]or in older men after a 3.5-day fast [45]. Several studies reported a decreased LH pulse frequency after only a 1-day [2, 3, 4, 5, 6]or a 2-day fast [19]in male rhesus macaques and after a 3.5-day fast in young men [45, 49]. However, in the latter study [43]the authors concluded that lower mean LH levels were due largely to a decrease in the amplitude of LH pulses.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with the observations in this study, LH pulse frequency was unchanged in obese men after a 10-day fast [46], in young men following either a 2-day [48]or a 5-day fast [44]or in older men after a 3.5-day fast [45]. Several studies reported a decreased LH pulse frequency after only a 1-day [2, 3, 4, 5, 6]or a 2-day fast [19]in male rhesus macaques and after a 3.5-day fast in young men [45, 49]. However, in the latter study [43]the authors concluded that lower mean LH levels were due largely to a decrease in the amplitude of LH pulses.…”
Section: Discussionsupporting
confidence: 87%
“…Differences in the physiological role of leptin between species could explain the discrepancies between our results in macaques and those in rodents [14, 43]. However, the reduced mean LH levels and decreased LH pulse frequency in adult [2, 3, 4, 5, 6]and peripubertal [19]rhesus monkeys observed during fasting are relieved in peripubertal male monkeys with recombinant human leptin treatment [19]. Interestingly, testosterone levels in leptin-treated animals were not different from those in fasted controls in that study [19].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, in ovariectomized female rats, a 120-hour fast induced a reduction in plasma mean LH concentration, but not pulse intervals. This inhibitory effect was reversed by nal oxone injections [10,41], In contrast, in intact male rhe sus monkeys, 1 day of fasting decreased both the mean LF1 pulse frequency and concentration but, in spite of a transient stimulation of LH release immediately after the initiation of the naloxone infusion, this opioid receptor antagonist was unable to restore the normal LH secretory pattern [42], Our results concerning the absence of significant effect of a 0.5-mg/kg/h naloxone infusion on the LH secretory pattern in long-term gonadectomized male rats, are in con trast with the one observed in experiments carried out in intact or in 1-to 2-weck-short-term gonadectomized rats. in which naloxone increased the plasma LH mean concen tration [43][44][45].…”
Section: Insulin-induced Hypoglycemia and Lh Secretion In Male Ratmentioning
confidence: 90%
“…Pirke & Spyra [6] first demonstrated that plasma LH concentrations are more reduced by testosterone in fasted males than in unfasted males and concluded that the testosterone feedback system is more sensitive in fasted males than in -Originalccumulating evidence suggests that starvation and malnutrition impair reproductive functions in both sexes in several mammalian species [1][2][3][4][5][6][7]. We have previously shown that pulsatile LH secretion is profoundly suppressed by 48-h fasting in female rats, and that this inhibition is enhanced by estrogen [8,9].…”
mentioning
confidence: 93%